ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENGGUNAAN LEMBAGA BANK SYARIAH: STUDI DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Donna, Duddy Roesmara (Jurnal Kawistara, 2012)
This research aims to analyze factors that affect the using of sharia nance institution in the Province of DIY. This research involved 150 respondents distributed throughout Yogyakarta City, Bantul Regency, Kulon Progo, Gunungkidul Regency, and Sleman Regency. A purposive non-probability sampling method was used to predict population behavior, with factor analysis as a tool of analysis. The preference of using sharia nance institution was affected by institution factor, including institutional ones, loyalty of Islamic law, service, and the suitability of product.